Topo-phylogeny: Visualizing evolutionary relationships on a topographic landscape - Waese, Jamie; Provart, Nicholas J.; Guttman, David S. (PLoS ONE, 2017)
Phylogenetic trees are the de facto standard for visualizing evolutionary relationships, but large trees can be difficult to interpret because they require a high cognitive load to identify relationships between multiple operational taxonomic units (OTUs). We present a new tool for displaying phylogenetic relationships as a topographic map in which OTUs autonomously attract or repel one another based on their individual branch lengths and distance to a common ancestor. This data visualization paradigm makes it possible to preattentively identify the nature of the relationship between items without having to trace a complex network of branches back to the root. This tool was developed for exploring phylogenetic data, but the technique could be extended for visualizing other hierarchical structures as well.